Sankofa pediatric HIV disclosure intervention did not worsen depression scores in children living with HIV and their caregivers in Ghana - Radcliffe, Christopher (BMC Public Health, 2020)
BACKGROUND: The ‘Sankofa’ pediatric HIV disclosure study (2013–2017) was an intervention that aimed to address the low prevalence of disclosure of HIV status in Ghana. METHODS: We conducted a cross-sectional study at the intervention site in Kumasi, Ghana, in 2019, (2 years after study closure) and administered the 21-item Beck Depression Inventory (BDI) and the 10-item Child Depression Inventory (CDI) to caregiver-child dyads who received the intervention. RESULTS: We enrolled 65% (N = 157) of the original dyads in the present study. Between Sankofa enrollment baseline and the present study, both children and caregivers had significant (p < 0.0001) mean reductions in CDI scores and BDI scores, respectively. CDI scores of the children were significantly correlated with BDI scores of the caregivers (r = 0.019, p = 0.019). No statistically significant associations between disclosure status and either CDI score or BDI score were found. CONCLUSIONS: Our findings did not support caregivers’ fears that disclosure leads to depression. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01701635 (date of registration Oct 5, 2012).